Response Surface Optimization of Setting Time and Compressive Strength of a Clay–Bauxite Geopolymer Binder for Oil-Well Cementing - Barima Money; Priyanga A/P Kailasanathan; Norasyikin Ismail; Abutu David; Siti Hajar Noor Shaarani; Norida Ridzuan; Siti Qurratu' Aini Mahat (Journal of Chemical Engineering Research Progress, 2026)
The development of sustainable cement alternatives has intensified interest in alkali‐activated binders formulated from abundant clay minerals. In this study, a clay-based geopolymer binder was synthesized and optimized by investigating the combined influence of activated clay loading (10-100 g), bauxite loading (0-150 g), alkaline activator dosage (0-3 g), and curing temperature (90-150 °C) on its setting time and compressive strength. A Central Composite Design (CCD) under Response Surface Methodology (RSM) was employed to model the responses and determine optimal processing conditions. The experimental results revealed that both responses were significantly influenced by the synergy between the activator dosage and raw material loading. Increasing activated clay and bauxite content accelerated geopolymerization, leading to shortened setting time, whereas excessive activator addition resulted in delayed matrix hardening due to excess soluble silicate–aluminate species. Compressive strength increased with increasing precursor loading up to a threshold level, beyond which incomplete dissolution restricted polycondensation. Regression analysis demonstrated excellent agreement between predicted and experimental values, with no transformation required, as confirmed by Box–Cox analysis. The normality and independence of residuals were verified through residual plots against predicted values and experimental runs. Optimization using a desirability function achieved a setting time of 6 h and compressive strength of 40.44 MPa at optimal conditions of activated clay (55 g), bauxite (75 g), activator dosage (1.5 g), and curing temperature (120 °C), with a global desirability of 1.000. These results confirm RSM as an effective statistical tool for tailoring the performance of clay-based geopolymers, offering a promising pathway for developing high-strength, fast-setting, sustainable binders. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).